Active and passive assets, their returns and the role of market efficiency - Steyn, Conrad (Department of Finance and Tax, 2025)
Passive investments, as a vehicle of fund allocation, have grown to comprise an increasingly significant portion of the global investment landscape, substantially due to the relative underperformance of active investments. Several prior studies have noted the existence of a relationship between the returns of active and passive investment styles and the relative fund flows to these styles. Limited literature exists which considers potential channels through which this relationship occurs. This study builds on existing literature by focusing on relative assets under management (AUM) in place of fund flows and examining a potential bi- directional relationship between relative AUM and relative returns. In addition, a channel through which relative AUM and relative returns are linked, that being market efficiency, is tested. The study employs a Vector Error Correction Model and uses data on the United States market, where the rise of funds under passive investment management has been most notable, over the period 2000 – 2019. A test for a direct relationship between relative return rankings and relative AUM is conducted and examined for bidirectionality. Following this, the postulated channel of market efficiency is tested for, directly and through the determinants of market efficiency (information and transactions costs), to assess the link through which relative AUM affect relative return rankings and vice versa. A long-run relationship is found between relative return rankings and relative AUM. In the short run, changes in relative return rankings do not influence changes in relative AUM while changes in relative AUM are a determinant of changes in relative return rankings. Both relative return rankings and relative AUM have a long-run relationship with the market efficiency measure. Interestingly, only relative return rankings is found to have a long-run relationship with the market efficiency determinants. The finding that relative return rankings and relative AUM have a long-run relationship, and that both have a long-run relationship with changes in market efficiency, provides support for a market efficiency-based channel in explaining the linkage between relative return rankings and relative AUM. The study's findings have important implications for fund managers and retail investors.